KOALISI PARTAI ISLAM DI INDONESIA PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 - Ekawati, Esty (Jurnal Penelitian Politik, 2015)
Political coalition is a necessity for a state, like Indonesia, that using multiparty system. Coalition is a mustsince the election could not provide a majority in a parliament. Some factors have determined the parties’ politicalbehavior in Indonesia and present two factors that would determine why were the coalition of Islamic political partiesdifficult to realize in the 2014 Presidential election. Firstly, political pragmatism has made Islamic polical partybecome cartel party in which party become agent of the state and employs the resources of the state to ensure thesurvival of the party. Secondly, Islamic political parties do not have popular figures against Prabowo and Jokowi.Keywords: political party, general election, coalition.